P41 Endoscopy in cerebellopontine angle lesions: feasibility and technical considerations. Issue 3 (14th February 2019) - Oesman, C; Alamri, A; Khalil, S; Wareing, M; Saeed, S; Bradford, R; Paraskevopoulos, D
Abstract : Objectives: To define selection criteria and describe technique nuances for the use of endoscopy in surgery for cerebello-pontine angle (CPA) lesions. Design: Prospective observational study. Subjects: Patients undergoing CPA lesion resection were selected for endoscope-assisted and/or endoscope-guided lesion resection. Methods: CPA interventions without mass lesions were excluded. 10 CPA lesions were identified pre-operatively for intra-operative endoscopic use across two neurosurgical centres. We describe equipment and technique selection. Results: 10 cases were selected over a one year period. Histology revealed 3 vestibular schwannomas (VS) (30%), 1 cyst (10%), 3 epidermoids (30%), 3 meningiomata (30%). Three cases were planned and carried out fully endoscopically (including two VS and the cyst) based on patient factors and favourable anatomy. Four cases were carried out with endoscopic assistance. The endoscope was used in three cases for anatomical orientation 'around the corner' only. Techniques and equipment vary depending on surgical aims, surgical anatomy and working area. Tips and pitfalls are identified and described. Conclusions: Endoscopy can be applied safely in CPA pathologies, as an alternative to the operating microscope for highly selected cases, or as an adjunct for specific surgical steps, especially when microscope optics do not allow angled visualisation. It is particularly useful in identifying lesion residuum and 'working around the corner'. High level training is required before applying endoscopy to the CPA.